Fostering Religious Character in Early Childhood Through Islamic Values and Daily Habits - Fhara Mutia; Ampun Bantali (Al-Qalam Institue, 2026)
This study aims to explore the implementation of character education based on Islamic values in shaping the religious attitudes of early childhood students. Using a qualitative case study approach, data were collected through observations, interviews, and documentation, and analyzed via data reduction, data presentation, and conclusion drawing. The findings indicate that internalization of key religious values honesty, discipline, and responsibility is achieved through habit formation, modeling, and integration of these values into daily learning activities. Children’s religious attitudes are observed in behaviors such as performing daily prayers, demonstrating politeness, and showing empathy toward others. Challenges include variations in family backgrounds, which may affect consistency in character development. The study highlights that fostering religious character in early childhood requires a holistic approach involving both family and school, supported by professional educators and institutional policies. The results underscore the importance of creating structured, consistent, and engaging strategies to nurture moral and spiritual growth, ensuring that children not only understand religious teachings but also practice them in daily life, forming the foundation of strong character from an early age.